2015
DOI: 10.1093/rpd/ncv467
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dependence of the Radiation Monitoring Instruments for Area Monitoring Used at Radiodiagnostic and Intervention Facilities

Abstract: Area monitoring is a fundamental test at radiodiagnostic facilities to maintain an acceptable level of radiation exposure for employees and members of the public. Experimental measurements were taken in an ionising radiation calibration laboratory. Four area monitor instruments were used. Dose and dose rate measurements were measured in integrated and rate operating modes. The results show that precautions are necessary where the area monitor uses exposure times of ≤2 s. When taking measurements in rate mode f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This deviation was found comparing this with measures on integrated dose mode, in ISO N 25 beam quality. Leyton et al [17] tested the same equipment in the same laboratory and found results with the same behavior. Differences between measures with dose rate and integrated dose mode, but this time using exposures with ISO N60, N80 and N100, which corresponds to 60, 80 and 100 kV of Tube voltage.…”
Section: Practicesmentioning
confidence: 81%
“…This deviation was found comparing this with measures on integrated dose mode, in ISO N 25 beam quality. Leyton et al [17] tested the same equipment in the same laboratory and found results with the same behavior. Differences between measures with dose rate and integrated dose mode, but this time using exposures with ISO N60, N80 and N100, which corresponds to 60, 80 and 100 kV of Tube voltage.…”
Section: Practicesmentioning
confidence: 81%